2022
DOI: 10.1186/s12978-022-01455-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of a single β-hCG test in predicting reproductive outcomes in women undergoing cleavage embryo transfer: a retrospective analysis from a single center

Abstract: Purpose The present study investigated the role of β-hCG in predicting reproductive outcomes and established optimal β-hCG cutoff values in women undergoing cleavage embryo transfer. Methods The patients were transferred with fresh or frozen-thawed embryos and had serum β-hCG levels tested on the 14th day post-embryo transfer. Serum β-hCG levels were compared between different groups. Different cutoff values of β-hCG were established and used to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
12
2
Order By: Relevance
“…This can be explained by the similar age of utilized oocytes as women older than 40 years are likely to have utilized donor oocytes and oocyte donors are usually younger than 30 years of age. The lack of association between age and serum β-hCG cutoff values is at variance with that reported [49,54] and could have resulted from the small sample size and high proportion of donor oocyte utilization in this population. Serum β-hCG had better discriminatory performance among cycles that utilized autologous oocytes compared with oocyte donor cycles.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This can be explained by the similar age of utilized oocytes as women older than 40 years are likely to have utilized donor oocytes and oocyte donors are usually younger than 30 years of age. The lack of association between age and serum β-hCG cutoff values is at variance with that reported [49,54] and could have resulted from the small sample size and high proportion of donor oocyte utilization in this population. Serum β-hCG had better discriminatory performance among cycles that utilized autologous oocytes compared with oocyte donor cycles.…”
Section: Discussioncontrasting
confidence: 67%
“…In addition, significant heterogeneity in the interval between embryo transfer and serum β-hCG reading could account for the variation between this study's cutoff and that reported by others. The interval varied by definition, that is, after oocyte retrieval [27,30,47] or after embryo transfer [43,44,46,48,49] . The interval also varied by duration, that is, 14-16 days after oocyte retrieval [27,30,45,47] and 12-16 days after embryo transfer [43,44,46,[48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, signi cant heterogeneity in the interval between embryo transfer and serum β-hCG reading, could account for the variation between this study's cut off and that report by others. The interval varied by de nition i.e, after oocyte retrieval [27,44,49] or after embryo transfer [43,45,48,50,51]. The interval also varied by duration i.e, 14-16 days after oocyte retrieval [27,44,47,49] and 12-16 days after embryo transfer [43,45,48,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The interval varied by de nition i.e, after oocyte retrieval [27,44,49] or after embryo transfer [43,45,48,50,51]. The interval also varied by duration i.e, 14-16 days after oocyte retrieval [27,44,47,49] and 12-16 days after embryo transfer [43,45,48,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation